PENGARUH MOBILE BANKING TERHADAP PROFITABILITAS BANK DI BURSA EFEK INDONESIA - Imamah, Nur; Safira, Dinda Ayu (FIA UB, 2021)
This study aims to determine the impact of mobile banking on bank profitability in Indonesia. The research sample consisted of 27 banks listed on the Indonesia Stock Exchange during 2015-2018. This study uses the dependent variable-return on assets (ROA), return on equity (ROE) and net profit margin (NPM), independent variable-mobile banking (m-banking), and control variables. This type of research is explanatory research by using panel data regression analysis or ordinary least square (OLS) method. The findings from the random effect model or generalized least square in this study are that mobile banking has a positive effect but statistically insignificant on ROA, ROA, and NPM. This implies that mobile banking in Indonesia can increase the profitability of banks by further increasing various digital innovations.